A dihydroindolizino indole derivative selectively stabilizes G-quadruplex DNA and down-regulates c-MYC expression in human cancer cells - Nagesh, Narayana; Raju, G.; Srinivas, R.; Ramesh, P.; Reddy, M. Damoder; Reddy, Ch. Raji (Biochimica et biophysica acta, 2015)
Telomeric and NHE III1, a c-MYC promoter region is abundant in guanine content and readily form G-quadruplex structures. Small molecules that stabilize G-quadruplex DNA were shown to reduce oncoprotein expression, initiate apoptosis and they may function as anticancer molecules. Electrospray ionization mass spectrometry, spectroscopy, isothermal titration calorimetry, Taq DNA polymerase stop assay, real time PCR and luciferase reporter assay. Cell migration assay to find out the effect of derivatives on normal as well as cancer cell proliferation. Among three different dihydroindolizino indole derivatives, 4-cyanophenyl group attached derivative has shown maximum affinity, selective interaction and higher stability towards G-quadruplex DNA over dsDNA. Further, as a potential G-quadruplex DNA stabilizer, 4-cyanophenyl linked dihydroindolizino indole derivative was found to be more efficient in inhibiting in vitro DNA synthesis, c-MYC expression and cancer cell proliferation among human cancer cells. The present study reveals that dihydroindolizino indole derivative having 4-cyanophenyl group has potential to stabilize G-quadruplex DNA and exhibit anticancer activity. These studies are useful in the identification and synthesis of lead derivatives that will selectively stabilize G-quadruplex DNA and function as anticancer agents. A series of dihydroindolizino indole derivatives were synthesized and their antitumor activity, ability to selectively interact and stabilize G-quadruplex DNA were studied. Results indicate that 4-cyanophenyl linked derivative (DHII-4CPh) is superior in all aspects. It is closely followed by thiophen-2-yl (DHII-TPh) and 3-methyl-1-phenyl-1H-pyrazol-4-yl (DHII-MPhPy) linked derivatives. [Display omitted] •We synthesised three different dihydroindolizino indole derivatives.•Studies indicate that, DHII-4CPh has better interaction with dimeric G-quadruplex formed by d(T2AG3)2 over dsDNA and stabilize it.•DHII-4CPh inhibit in vitro DNA synthesis with an increase of DHII-4CPh concentration.•DHII-4CPh reduced c-MYC expression and brings down cancer cell proliferation.